2011
DOI: 10.1111/j.1365-2702.2011.03745.x
|View full text |Cite
|
Sign up to set email alerts
|

The views of mental health nurses on continuing professional development

Abstract: Findings from this study highlight the value clinical nurses place on having access to work-based and clinically focussed education and development. Relevant on-the-job professional education has the potential to improve job satisfaction and retention of clinical nurses, thus ultimately directly and positively influence patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 21 publications
2
28
0
Order By: Relevance
“…Various mobile learning applications have already been developed and can be downloaded from application stores. Mobile learning has recently become a popular format for the delivery of continuing education to healthcare professionals and students (Cleary et al, 2011;Lahti et al, 2013). It has been extended to various medical education fields, including dermatology (Rajasekaran and Iyengar, 2013), surgery (de Sena et al, 2013), and nursing (Walton et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Various mobile learning applications have already been developed and can be downloaded from application stores. Mobile learning has recently become a popular format for the delivery of continuing education to healthcare professionals and students (Cleary et al, 2011;Lahti et al, 2013). It has been extended to various medical education fields, including dermatology (Rajasekaran and Iyengar, 2013), surgery (de Sena et al, 2013), and nursing (Walton et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A study carried out with nurses with mental health experience in Australia revealed that among the factors that encouraged them to stay in the current health service were the flexibility of the service for taking courses and the opportunity to be absent for study purposes, showing the importance of training in the professional development plans of these nurses (8) .…”
Section: Discussionmentioning
confidence: 99%
“…And "functions" include the social actions and various processes developed by professionals in order to reinsert the person with mental disorder and/or user of psychoactive substance in the family and society (7) . In this sense, the psychiatric nursing sought to adopt new theoretical and methodological references based on relationship and therapeutic communication (8) , expanding its scope of actions to the psychosocial and community model through activities in groups, workshops, among others.…”
Section: Introductionmentioning
confidence: 99%
“…8,10,11 Other healthcare professions, including medicine, nursing, dentistry, and allied health, are utilizing the CPD process to actively maintain and improve their knowledge and skills. [12][13][14][15] Accumulating CPE hours without any sort of planning for the content or form is unlikely to result in long-term, positive outcomes. 12,14 Dental professionals in the United Kingdom have followed a required CPD process for more than 10 years.…”
Section: Continuing Professional Development (Cpd)mentioning
confidence: 99%